Development of Unique Xanthene–Cyanine Fused Near‐Infrared Fluorescent Fluorophores with Superior Chemical Stability for Biological Fluorescence Imaging. Issue 2 (11th November 2014) - Chen, Hua; Lin, Weiying; Cui, Haijun; Jiang, Wenqing
Abstract The development of near‐infrared (NIR) functional fluorescent dyes has gained increasing attention over the last few decades. Herein, we describe the development of a unique type of xanthene–cyanine fused NIR fluorophores, XC dyes, formed by reacting chloro‐substituted cyanine with resorcin or its analogues under anhydrous conditions. XC dyes are a hybrid of cyanine and xanthene. The preliminary mechanistic studies indicate that the formation of XC compounds likely includes a sequence of cyclization and oxidation. XC dyes have absorption and emission in the NIR region, and their fluorescence properties can be controlled by modifications of the key hydroxyl and amine groups. The novel XC NIR dyes are advantageous over previously developed merocyanine dyes NIR dyes in their chemical stability against strong nucleophiles. Quantum chemical calculations reveal that the distinct properties of XC and HD dyes can be attributed to their structural differences. By taking advantage of the superior properties of XC dyes, we have further constructed a new NIR fluorescent probe, XC‐H2S, which is capable of monitoring both the concentration‐ and time‐dependent variations of H2S in living animals, highlighting the value of XC NIR dyes. We expect that the unique XC NIR dyes developed herein will find broader applications than HD NIR dyes as fluorescent platforms for the development of a wide variety of NIR fluorescent probes, in particular, those suitable for targets of interest that have strong nucleophilic character.